Energy storage for power systems - Ter-Gazarian, A. (Andrei); Institution of Engineering and Technology (London : Institution of Engineering and Technology, 2011)
The supply of energy from primary sources is not constant and rarely matches the pattern of demand from consumers. Electricity is also difficult to store in significant quantities. Therefore, secondary storage of energy is essential to increase generation capacity efficiency and to allow more substantial use of renewable energy sources that only provide energy intermittently. Lack of effective storage has often been cited as a major hurdle to substantial introduction of renewable energy sources into the electricity supply network. The author presents here a comprehensive guide to the different types of storage available. He not only shows how the use of the various types of storage can benefit the management of a power supply system but also considers more substantial possibilities that arise from integrating a combination of different storage devices into a system. This book will be important to those seeking to develop environmentally sound energy resources.
The use of energy storage -- Energy storage techniques -- Power system considerations for energy storage.
Includes bibliographical references and index.
Keywords: Energy storage; Power-plants.